Landscape’s Narrative: Doing the Malcolm Lowry Walk - Ravvin, Norma (Studies in Canadian Literature, 1998)
Under the Volcano was substantially rewritten numerous times, rejected by publishers in a variety of forms, but found its final shape while Malcolm Lowry and his wife lived in a squatter’s shack on the shore of Burrard Inlet in Vancouver. The longer Lowry lived there, the more complex his fictional ruminations on the landscape became. The landscape was for Lowry, to use the words of American historian Simon Schama, "a text on which he wrote his "recurring obsessons." The shores of Burrard Inlet can still be explored to recover the myth and memory that lie beneath the surface of the place.